Pendidikan Ekonomi Informal: Bagaimana Pendidikan Ekonomi Membentuk Pengetahuan Pada Bisnis Keluarga? - Hasan, Muhammad (Universitas Negeri Makassar, 2018)
This article examines aspects of knowledge transfer in family business that are implemented in informal economic education through Bandura's social cognitive theory model. This study uses literature studies by looking for theoretical references that are relevant to the case or problem found. The results of this study indicate that economic education forms knowledge in family business through the role of modeled behavior and will be studied in observational learning. The observational learning process itself is governed by four interrelated components, namely the process of attention, the process of retention, the process of motor reproduction, and the process of motivation